One approach to the design of individual mathematical models of security in wireless sensor networks - Kotukh, Y.V.; Lyubchak, V.O.; Strakh, O.P. (Radiotekhnika, 2021)
The current level of development of engineering and technology is characterized by a constant expansion of the variety and complexity of mechanical and controlled objects, the operation of which occurs in a continuous-discrete time mode. One of these objects is the process of spreading malicious software in wireless sensor networks, the constant growth of trends towards which is due to their use as a single type of self-organized data transmission network with the least labor intensity and low cost. The concept of building sensor networks has not been formed at all. Therefore, the study of certain properties of such networks is very important for both domestic and world science. Moreover, for the strategically important sectors of the country, in particular defense, the protection of wireless sensor networks is a very important component. A new model of malware distribution is proposed, which is described by some boundary value problem for an impulsive dynamical system on a time scale.